2013
DOI: 10.3382/ps.2013-03091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo feeding of carbohydrates on hatchability, body weight, and energy status in domestic pigeons (Columba livia)

Abstract: The effects of in ovo feeding of carbohydrates on hatchability, BW, yolk sac weights (YSW), pectoral muscle weights (PMW), liver and pectoral muscle glycogen concentration, serum glucose level, and hepatic glucose-6-phosphatase activity of domestic pigeons, hatched from eggs laid by a 40-wk-old breeder flock, were investigated. At 14.5 of incubation, fertile eggs were injected with 200 μL of 1.5% maltose (M) + 1.5% sucrose (S), 2.5% M + 2.5% S, 3.5% M + 3.5% S, or 4.5% M + 4.5% S in 0.75% saline, with controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
5
23
0
2
Order By: Relevance
“…Therefore, the higher residual yolk sac may be beneficial to the development and growth of neonatal broilers in this study. However, another research revealed that IOF of carbohydrates decreased the yolk sac weight and increased the yolk sac nutrient utilization in domestic pigeons (Dong et al., ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the higher residual yolk sac may be beneficial to the development and growth of neonatal broilers in this study. However, another research revealed that IOF of carbohydrates decreased the yolk sac weight and increased the yolk sac nutrient utilization in domestic pigeons (Dong et al., ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results of different studies report both negative and positive effects of the in-ovo injection of substances on hatchability. Hatchability was increased by in-ovo injection with ascorbic acid (Ipek et al, 2004), L-arginine (Al-Daraji et al, 2012), and carbohydrates (Dong et al, 2013). However, hatchability was reduced by in-ovo injection with ascorbic acid (Sgavioli et al, 2015), organic trace minerals (Oliveira et al, 2015), glucose (Ebrahimnezhad et al, 2011), and glucose and magnesium (Salmanzadeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the current results showed that absolute BW at hatch, BW, FI and FCR at day 7 and 14 was not affected by any injection treatments ( p > .05), but numerally, as compared with the control, BW and FCR were improved by IYSI of albumin (Table ). A large amount of studies have reported that in ovo injection of different nutrients into different sites of eggs and at variable time of incubation, increases (Dong, Jiang, Wang, Wang, & Zou, ), decreases (Chamani et al., ; Moghaddam, Borji, & Komazani, ; Salmanzadeh, ) or does not have any significant effects (Eslami et al., ; Keralapurath, Corzo, Pulikanti, Zhai, & Peebles, ; Ohta, Tsushima, Koide, Kidd, & Ishibashi, ; Shafey et al., ; Zhai, Bennet et al., ); Zhai, Gerard et al., on hatch percentage. Therefore, the efficiency of in ovo injection on hatchability is still under discussion due to an open debate about the optimum site and time of injection and the appropriate nutrient and volume of injected solution.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the efficiency of in ovo injection on hatchability is still under discussion due to an open debate about the optimum site and time of injection and the appropriate nutrient and volume of injected solution. In addition, hatch percentage numerally decreased by IYSI of dextrose which could be attributed to an overload bar of energy metabolism in broiler embryos by injecting high levels of carbohydrate that its adverse effects suggested that injection solution concentration must be limited to prohibit excessive energy metabolism of the embryo and further reduction in hatch percentage (Dong et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation